The influence of tourism on the development of the Rogaška Slatina health resort - Horvat, Uroš (Geografski zbornik, 2001)
The author uses the example of a health resort with a long history to discuss the effects of tourism on the development and structure of a settlement that developed in the mid 19th century into one of the most important tourist areasin Slovenia and went on to strengthen its role in a relatively poorly developed region through the development of industry and other urban activities. The first part of the article discusses the various phases of the health resort's development and the features of the tourist visits in Rogaška Slatina. The emphasis is on its dependance on tourist supply and demand as well as on changing economic, social, and political circumstances. The second part deals with the demographic, economic, and spatial development of the settlement. In as far as Rogaška Slatina is a multi-functional tourist area, the emphasis is on the influence of health and tourism-related activities as well as on industry, on the development and structure of employment, on the dynamics of population growth, and on the economic structure of the populationand households. Individual functional zones in Rogaška Slatina are defined, particularly those in which tourism and recreation represent the dominant type of land-use.
Keywords: Rogaška Slatina; tourism; turistična geografija; turizem; zdravilišča